2018
DOI: 10.1097/md.0000000000010571
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of survivin in patients with glioma

Abstract: Background:The aim of this study was to systematically evaluate the prognostic role of survivin in patients with glioma through performing a meta-analysis.Methods:PubMed, Web of Science, Cochrane Library, and EMBASE were searched for potentially eligible literature. The study characteristics and relevant data were extracted. Hazard ratios (HRs) with 95% confidence intervals (CIs) were pooled to estimate the prognostic role of survivin in patients with glioma.Results:Sixteen studies with 1260 patients were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…the main factors that affect OS in glioma patients were tumor characteristics, [ 26 ] whereas they were similar between the 2 groups, which might weaken the effect of RTBC program.…”
Section: Discussionmentioning
confidence: 99%
“…the main factors that affect OS in glioma patients were tumor characteristics, [ 26 ] whereas they were similar between the 2 groups, which might weaken the effect of RTBC program.…”
Section: Discussionmentioning
confidence: 99%
“…We found high levels of survivin expression in U251MG cells compared to normal astrocytes. It was suggested that higher survivin expression was associated with worse overall survival in patients with glioma [32]. Recently, survivin has attracted attention as a therapeutic target molecule for glioma [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Survivin localizes to the mitotic spindle and participates in regulating mitosis. In addition to GE cancers, it is highly expressed in various other malignancies and is associated with inferior outcomes including a shorter survival period (13)(14)(15). CENPF gene encodes centromere protein F that associates with the centromere-kinetochore complex.…”
Section: Discussionmentioning
confidence: 99%